Effect of Palmaris Longus on Handwriting Skills - Shukri, Mohammed Emad Ghanem; Hameed, Ahmed Fakhir; Marzook, Ahmed Abed; Yasser A. Alsharqi (AL-Kindy College Medical Journal, 2023)
Background: Kinesiologists, Physical Anthropologists, and Anatomists have all long been captivated by the structure and development of the superficial forearm flexor, the Palmaris longus. Objective: To study the effect of Palmaris Longus on certain handwriting skills. Subjects and Methods: Three Palmaris Longus occurrence tests were conducted on 200 students (100 males and 100 females) affiliated to Colleges of Medicine of Baghdad University then the participants were tested for certain handwriting skills to correlate the presence of Palmaris Longus in the dominant side with handwriting. Results: 89% of all subjects (178 subjects) and 91% of males were right-handed. Dominant Palmaris Longus among males (61%) was significantly higher than that of females (30%). Regarding the Motor assessment scale; female participants achieved good and it was significantly higher than that of males (23%). There was a significant association between left Palmaris Longus only and acceptable horizontal line assessment. Good sentence composition was noticed significantly in dominant Palmaris Longus. Conclusions: Variation of presence of Palmaris Longus in both sexes in the studied group meets with normal recorded variation. Presence of Palmaris Longus in the dominant forearm has correlation with good certain skills of handwriting skills.